Role of Cultural and Environmental Factors in Tourists’ Satisfaction: A Study of French-Speaking Health Tourists - Mohammad Faisal; Devendra Kumar Dhusia (ASEAN Journal on Hospitality and Tourism, 2026)
This study investigates the impact of cultural and environmental factors—specifically cultural opportunities, environment and destination management, hospitality, and physiography—on the satisfaction of French-speaking health tourists who have visited or are currently visiting India. Recognising that health tourism satisfaction is a multi-faceted concept influenced by a range of factors, including cultural and environmental aspects, this research aims to contribute to the understanding of these nuanced influences in the Indian context. Data were collected from 83 respondents through online and offline surveys, employing purposive and snowball sampling techniques. After data cleaning, 81 valid responses were analysed using Structural Equation Modelling with SmartPLS. The findings underscore that among the four independent constructs examined, cultural opportunities exert the strongest influence on the satisfaction of French-speaking health tourists, followed by physiographical attributes and hospitality factors. Accordingly, marketers should meticulously design itineraries that prioritise opportunities for immersive cultural engagement, showcase the region's natural beauty and diverse landscapes, and foster authentic hospitality experiences.